2018
DOI: 10.21660/2018.43.3546
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Parameter of Self Purification Process in the Urban Area of Cikapundung River, Indonesia

Abstract: Self-purification process is an important process in the effort of recovering the river condition itself. This process usually takes place naturally. However, several inhibitions might disturb the process. It was indicated by the slow deoxygenation rate and unhealthy river condition. This research aims to identify the influence parameters responsible for the slow of self-purification in the Cikapundung River, which is located in the urban area of Bandung City, Indonesia. The river water samples were taken and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…The deoxygenation rate value obtained in this research is higher than those of the previous studies. Cikapundung River study that used laboratory observations for 10 days obtains the value of the deoxygenation rate ranges from 0.01 to 0.37 per day (Yustiani et al, 2018). A study at the Cicadas River water shows a deoxygenation rate ranging from 0.01 to 0.17 per day (Yustiani et al, 2019).…”
Section: Calculation Results Of Thomas' Slope Methodsmentioning
confidence: 99%
“…The deoxygenation rate value obtained in this research is higher than those of the previous studies. Cikapundung River study that used laboratory observations for 10 days obtains the value of the deoxygenation rate ranges from 0.01 to 0.37 per day (Yustiani et al, 2018). A study at the Cicadas River water shows a deoxygenation rate ranging from 0.01 to 0.17 per day (Yustiani et al, 2019).…”
Section: Calculation Results Of Thomas' Slope Methodsmentioning
confidence: 99%
“…The low temperature severely inhibits the microbial activity since most heterotrophic microorganisms responsible for transforming dissolved organic matter to CO 2 are mesophilic, with an optimal metabolism at temperatures between 20-35 °C. Therefore, there are the minimum acceptable conditions to biodegrade the organic matter and nutrients (Yustiani et al, 2018;Zhou et al, 2018).…”
Section: Calculation Of Deoxygenation K D and Reaeration K R Constantsmentioning
confidence: 99%
“…Open defecation is mainly practiced by people who live in slum areas nearby the river, which causes water quality deterioration in the Cikapundung river, a tributary of the Citarum River. Because of excess discharge of untreated domestic wastewater, the Citarum river is classified as in the top 10 worst polluted rivers in the world [15][16][17]. Meanwhile, results from the household questionnaire surveys showed that only 37.47% of the population were served by septic tanks and the septage sludge generated from these tanks was properly emptied, collected by either PDAM or private companies and legally dumped at designated dumping points connected to sewer networks.…”
Section: Shit Flow Diagram (Sfd)mentioning
confidence: 99%